Hydroxyl Functionalized Pyridinium Ionic Liquids: Experimental and Theoretical Study on Physicochemical and Electrochemical Properties - Lethesh, Kallidanthiyil Chellappan; Evjen, Sigvart; Raj, Jaganathan Joshua; Roux, Denis C. D.; Venkatraman, Vishwesh; Jayasayee, Kaushik; Fiksdahl, Anne (Frontiers in Chemistry, 2019)
Structurally modified hydroxyl functionalized pyridinium ionic liquids (ILs), liquid at room temperature, were synthesized and characterized. Alkylated N-(2-hydroxyethyl)-pyridinium ILs were prepared from alkylpyridines via corresponding bromide salts by N-alkylation (65-93 %) and final anion exchange (75-96%). Pyridinium-alkylation strongly influenced the IL physicochemical and electrochemical properties. Experimental values for the ILs physicochemical properties (density, viscosity, conductivity and thermal decomposition temperature), were in good agreement with corresponding predicted values obtained by theoretical calculations. The pyridinium ILs have electrochemical window of 3.0 -5.4 V and were thermally stable up to 405 ºC. The IL viscosity and density were measured over a wide temperature range (25-80 ºC). Pyridine alkyl-substitution strongly affected the partial positive charge on the nitrogen atom of the pyridinium cations, as shown by charge distribution calculations. On-going studies on Mg complexes of the new ILs demonstrate promising properties for high current density electrodeposition of magnesium.